Consensus of multi-agent systems via hybrid impulsive protocols with time-delay. (November 2018) - Liu, Xinzhi; Zhang, Kexue; Xie, Wei-Chau
Abstract: This paper studies consensus problems of multi-agent systems. A novel hybrid consensus protocol with dynamically changing interaction topologies is designed to take the time-delay into account in both the continuous-time communication among agents and the instant information exchange at discrete-time moments. By using a new Halanay-type inequality and an auxiliary function, sufficient conditions are established to guarantee that the proposed consensus protocols lead to average-consensus. Our consensus criteria show that the networked multi-agent system with time-delay can achieve average-consensus with appropriate network topologies, suitably designed impulsive instants, and admissible time delays. Numerical simulations are provided to demonstrate the effectiveness of the theoretical results.